2016
DOI: 10.1515/popets-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Verifiable Range and Closest Point Queries in Zero-Knowledge

Abstract: Abstract:We present an efficient method for answering one-dimensional range and closest-point queries in a verifiable and privacy-preserving manner. We consider a model where a data owner outsources a dataset of keyvalue pairs to a server, who answers range and closestpoint queries issued by a client and provides proofs of the answers. The client verifies the correctness of the answers while learning nothing about the dataset besides the answers to the current and previous queries. Our work yields for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We also mention a large body of work devoted to authenticated data structures [26,32,30,29,27,12]. We insist that these result address a different problem than ours as they stand in the three party setting.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…We also mention a large body of work devoted to authenticated data structures [26,32,30,29,27,12]. We insist that these result address a different problem than ours as they stand in the three party setting.…”
Section: Introductionmentioning
confidence: 71%
“…For this reason, we focus on the two-party setting which is usually more challenging and results in less efficient schemes. Our protocols are indeed less efficient than the range queries of Ghosh et al [12] -which, to our knowledge, is the best size-hiding construction handling range queries in the three-party setting -but they do not assume a trusted committer.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Existing proposals in the literature all require weakening the notion of privacy to achieve range queries. In a three-party setting with trusted data owner, called a committer, and a third party who acts as the prover, a solution for zero-knowledge one-dimensional range queries was proposed by Ghosh et al [90]. Alternatively, if we allow a polynomial-sized upper bound on the database size to be revealed, Ostrovsky et al [166] showed that efficient zero-knowledge d-dimensional orthogonal range queries (d ≥ 1) is possible.…”
Section: Motivationmentioning
confidence: 99%
“…We recall the notion of canonical coverings from Ghosh et al [90], who used it to achieve zero-knowledge range queries in the three-party setting. For some set of leaves…”
Section: Binary Trees and Zero-knowledge Elementary Databasesmentioning
confidence: 99%